2022
DOI: 10.3389/fonc.2022.916018
|View full text |Cite
|
Sign up to set email alerts
|

Partial Nephrectomy Versus Radical Nephrectomy for Endophytic Renal Tumors: Comparison of Operative, Functional, and Oncological Outcomes by Propensity Score Matching Analysis

Abstract: PurposeThe study aimed to compare operative, functional, and oncological outcomes between partial nephrectomy (PN) and radical nephrectomy (RN) for entophytic renal tumors (ERTs) by propensity score matching (PSM) analysis.MethodsA total of 228 patients with ERTs who underwent PN or RN between August 2014 and December 2021 were assessed. A PSM in a 1:1 ratio was conducted to balance the differences between groups. Perioperative characteristics, renal functional, and oncological outcomes were compared between g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Only the increase in the postoperative creatinine value compared to the preoperative value showed a significantly higher increase in the TALA group compared to the RP group (p = 0.035), possibly due to higher percentage of TN performed in the TALA group compared to the RP group (11:9). It is known that TN has a significantly higher risk of acute renal Injury in the short-term interval of 48 h postoperative and progression to chronic renal failure in the long-term interval of up to one year following surgery [11].…”
Section: Discussionmentioning
confidence: 99%
“…Only the increase in the postoperative creatinine value compared to the preoperative value showed a significantly higher increase in the TALA group compared to the RP group (p = 0.035), possibly due to higher percentage of TN performed in the TALA group compared to the RP group (11:9). It is known that TN has a significantly higher risk of acute renal Injury in the short-term interval of 48 h postoperative and progression to chronic renal failure in the long-term interval of up to one year following surgery [11].…”
Section: Discussionmentioning
confidence: 99%
“…This proximity makes it particularly important to repair these structures with traditional suturing techniques after damage during surgery, which is di cult to achieve with generally less invasive sutureless techniques. Studies have shown that partial nephrectomy for large or endophytic tumors involves longer operative times and a higher risk of surgical complications compared to radical nephrectomy [22][23][24].…”
Section: Discussionmentioning
confidence: 99%